2014
DOI: 10.4103/0259-1162.134494
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of subarachnoid block by intravenous dexmedetomidine for sub umbilical surgical procedures: A prospective control study

Abstract: Background:Intravenous dexmedetomidine is used as adjuvant during general anesthesia due to its sedative and analgesic effects. The present study was aimed to evaluate the effects of intravenous dexmedetomidine on sensory and motor block characteristics, hemodynamic parameters and sedation during subarachnoid block.Materials and Methods:In this double-blind randomized placebo control study, 60 patients of American Society of Anesthesiologist I and II were randomized into two groups by computer generated table.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 14 publications
4
23
0
Order By: Relevance
“…In the present study, no significant differences were observed in the percentage of patients administered the cardiovasoactive drugs between the two groups, and the loading dose set to 3 μg/kg/h in our protocol may have influenced this result. Nevertheless, previous studies indicated that bradycardia was transient and easily reversed with intravenous atropine [10] [11] [12] [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no significant differences were observed in the percentage of patients administered the cardiovasoactive drugs between the two groups, and the loading dose set to 3 μg/kg/h in our protocol may have influenced this result. Nevertheless, previous studies indicated that bradycardia was transient and easily reversed with intravenous atropine [10] [11] [12] [20].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated the onset time of sensory block after spinal anaesthesia, Readdy et al have compared intravenous dexmedetomidine with clonidine reported that dexmedetomidine shortened onset of sensory-motor block [41] but other studies are not supporting the faster onset of sensory/motor block [12,13,[27][28][29][30]. Few study have reported intravenous dexmedetomidine shortened the onset time by 30-60 sec, which might be clinically significant but it was insignificant statistically [11,33,35].…”
Section: Onset Of Sensory/motor Blockadementioning
confidence: 99%
“…Sensory block duration -though there are too much variation in method and dose of intravenous dexmedetomidine and duration of sensory blockadebut most of the studies has reported significantly increased duration of sensory blockade by use of intravenous dexmedetomidine [11][12][13][28][29][30][31][32][33][34][35]37,38,42]. Only one study did not find any difference in block quality with the use of low dose dexmedetomidine infusion that was used solely for the purpose of intraoperative sedation [36].…”
Section: Duration Of Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] study showed a faster onset of sensory blockade with a time of 2.91 ± 1.16 min whereas Gupta et al . [9] study attained T10 sensory blockade at 3.1 ± 1 min. This difference from our study might be due to the difference in the dosage pattern in other studies when compared to our study.…”
Section: Discussionmentioning
confidence: 99%